Potential environmental pollution and human health risk assessment due to leachate contamination of groundwater from anthropogenic impacted site - Omobolaji, O. Afolabi; Elekwachi, Wali; Eze, C. Ihunda; Maureen, C. Orji; Victoria, O. Emelu; Lilian, C. Bosco-Abiahu; Nnamdi, C. Ogbuehi; Sunny ,O. Asomaku; Odinaka ,A. Wali (Environmental Challenges, 2022)
One of the consequences of landfill systems is the emission of leachate, which is capable of causing contamina- tion of the surrounding environment, including groundwater. Considering three major abandoned landfills in an urban area in Nigeria, the potential environmental pollution due to leachate generated from landfills and hu- man health risk assessment of nearby groundwater were examined using laboratory standards (APHA 2012). The result revealed that the landfills’ leachate pollution index (LPI) is 18.84, 19.57, and 19.66, indicating potential pollution of the environment, including groundwater and soil. Conformity of groundwater indicated that Arsenic (Ar-0.0001), Cadmium (Cd-0.002), Zinc (Zn-0.02), Barium (Ba-0.03), Manganese (Mn-0.05), Copper (Cu-0.02, 0.012), Chromium (Cr-0.006, 0.007), and Cobalt (Co-0.03, 0.015) are within the WHO permissible limit while Nickel (Ni-0.06) and Lead (Pb-0.05) exceeded the permissible limit. Using the USEPA model for human health risk assessment, the Total Hazard quotient (THQ) for ingestion and derma exposure indicated that the heavy metals have ≤ 1 across the three landfills, indicating that the exposed population experience no significant health risk. The THQ trended as Cd > Co > Zn > Ba > Mn > Cu > Cr > Ni > As > Pb for children across all the landfills. The estimation for Total Carcinogenic Risk (TCR) for carcinogenic metals (As, Cd, Cr, Ni, and Pb) from various landfill indicated no carcinogenic risk (TCR < 10 − 6 ). Although the abandoned landfills showed potential environmental pollution and contamination of groundwater; however, the health risk assessment of the groundwater revealed no signifi- cant carcinogenic risk to the population exposed to it. Hence, the need for water treatment and evaluation of the soil contamination status of landfills.
Keywords: Environmental pollution Human health risk Leachate pollution index Groundwater Carcinogenic Metals